1974
DOI: 10.1111/j.1550-7408.1974.tb03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transport in the Malarial (Plasmodium lophurae) Infected Erythrocyte*

Abstract: SYNOPSIS Plasmodium lophurae‐infected red blood cells utilized considerably greater quantities of glucose than did uninfected duckling red cells. Kinetic analysis of glucose transport showed: (A). Below a concentration of 2 mM in the medium the uptake process followed Michaelis‐Menten kinetics (carrier‐mediated facilitated diffusion) whereas at concentrations greater than this simple diffusion became the main mode of entry. (B). The apparent transport constants, Kt, for normal and infected cells were similar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Malaria‐infected human and avian RBCs also show increased transport of a variety of non‐electrolytes [5,7]. There is also good evidence for enhanced sorbitol and taurine uptake into malaria‐infected chicken RBCs under physiological conditions via a malaria‐induced pathway [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria‐infected human and avian RBCs also show increased transport of a variety of non‐electrolytes [5,7]. There is also good evidence for enhanced sorbitol and taurine uptake into malaria‐infected chicken RBCs under physiological conditions via a malaria‐induced pathway [23].…”
Section: Resultsmentioning
confidence: 99%
“…New permeation pathways (NPP) exist in human [5] and murine malaria‐infected RBCs [6] and a reanalysis of earlier work [7] suggests their presence in malaria‐infected avian RBCs. Kirk and co‐workers [5] reported that the NPP in malaria‐infected human RBCs are broad‐specificity pathways of a single type, which show the characteristics of an anion channel.…”
Section: Introductionmentioning
confidence: 99%
“…Such is the case for the myo-inositol required for the synthesis of phosphatidylinositol (Vial, Thuet & Philippot, 1982), for lactate which is the main waste product of the energy metabolism of the infected cell (Pfaller et al, 1982) and for several amino acids which the parasite has to import from the extracellular space (Sherman, 1979). One was, therefore, not surprised to find that the membrane of the infected cell is highly permeable to amino acids (Sherman & Tanigoshi, 1974b), hexoses (Homewood & Neame, 1974;Sherman & Tanigoshi, 1974a), myo-inositol (Elford et al, 1985) and polyols (Lambros & Vanderberg, 1979). Recently, a thorough survey has been performed of the permeability pattern of human erythrocytes, infected with Plasmodium falciparum to anions, carbohydrates and amino acids (Kutner, Ginsburg & Cabantchik, o.5, 1983;Ginsburg et al, 1983Ginsburg et al, , 1985.…”
Section: Permeability Changes In Malaria-infected Erythrocytesmentioning
confidence: 96%
“…Erythrocytes parasitized with P. berghei and P. lophurae actually catabolize glucose at rates exceeding its rate of entry into unparasitized host cells. The plasmodia have solved this dilemma by bringing about an increase in the rate at which glucose enters the parasitized erythrocyte (299,371). The related blooddwelling Babesia rodhaini brings about a similar change in its mouse erythrocyte host (195).…”
Section: Modes Of Multiplicationmentioning
confidence: 99%